Unveiling Success: An Exploration of Self-directed Learning among TOSE Students - Endah Susaeni; Endang Fauziati; Endang Setyningsih (South Sulawesi Education Development (SSED), 2024)
This study explores the Self-Directed Learning (SDL) strategies employed by successful students preparing for the Test of Standard English (TOSE) at an Indonesian university, using Garrison's (1997) SDL model as a framework. The research focuses on three dimensions of SDL: self-management, self-monitoring, and motivation. Data were collected through semi-structured interviews with threeTOSE students, revealing key findings about their motivational drivers, organizational strategies, and reflective practices. The results indicate that students exhibit both entering motivation rooted in a desire to achieve high scores and avoid failure and task motivation, which is influenced by long-term career aspirations and the need for timely graduation. Additionally, participants employed effective self-management techniques, such as setting clear learning objectives and utilizing AI tools for practice, while also engaging in metacognitive strategies to monitor their progress. The study highlights the importance of balancing self-directed efforts with external feedback and guidance from educators. These insights contribute to a deeper understanding of SDL in language proficiency testing contexts and offer practical recommendations for enhancing student learning strategies in high-stakes assessments. Future research should aim to broaden the participant pool and investigate the role of AI tools in supporting diverse learning preferences.